On the possibility of the existence of the spatially periodical Bose condensate - Peletminsky, A.S.; Peletminsky, S.V.; Slyusarenko, Yu.V. (Condensed Matter Physics, 2000)
The possibility of constructing the theory relating to a spatially periodical
Bose condensate in the model of a weakly nonideal Bose gas is studied. Equations for determining a spatially periodical order parameter at the
temperature T = 0 are formulated and their one-periodical solutions are
obtained based on the isolated Bose condensate method. Here it is possible to neglect the contribution of quasiparticles to the thermodynamics of
a boson system. The problems of thermodynamic stability of the spatially
periodical Bose condensate are presented in short. У роботi вивчено можливiсть побудови теoрiї просторово-перiодичного бозе-конденсату в моделi слабконеiдеального бозе-газу. На основi методу видiленого бозе-конденсату сформульовано рiвняння
для визначення просторово-перiодичного параметра порядку при
температурi T = 0 , коли можна знехтувати внеском квазiчастинок до термодинамiки системи бозонiв, та знайдено їх одноперiодичнi розв’язки. Коротко викладено питання термодинамiчної стiйкостi просторово-перiодичного бозе-конденсату.